Dye-sensitized photocatalytic hydrogen production: distinct activity in a glucose derivative of a phenothiazine dye. Issue 43 (11th April 2016) - Manfredi, N.; Cecconi, B.; Calabrese, V.; Minotti, A.; Peri, F.; Ruffo, R.; Monai, M.; Romero-Ocaña, I.; Montini, T.; Fornasiero, P.; Abbotto, A.
Abstract : A glucose-functionalized phenothiazine dye gave efficient activities compared to the common hydrophilic triethylene glycol derivative as a consequence of improved wettability and peculiar features of the sugar functionality. Abstract : A thiophene-based donor–acceptor phenothiazine dye has been functionalized with a peripheral glucose unit (PTZ-GLU) to bust its affinity to water and enhance dye-sensitized photogeneration of hydrogen. Compared to the corresponding alkyl derivative (PTZ-ALK), as well as the common hydrophilic triethylene glycol substitution (PTZ-TEG), the sugar derivative shows a lower contact angle; PTZ-GLU performed twice more efficient than PTZ-TEG in the photogeneration of hydrogen in terms of evolved gas and turnover number.